Multidimensional analysis and enhancement strategies for ecological environment quality at the county level under dual carbon goals: a case study of Shaanxi Province, China - Li, Jianfeng; Hu, Yongxin; Li, Jian; Yang, Liangyan; Yan, Jie (Frontiers in Environmental Science, 2025)
With the intensification of global climate change and environmental degradation, the goals of carbon peaking and carbon neutrality have become crucial strategies for promoting sustainable development in various countries. However, most studies on ecological environment quality (EEQ) focus on urban areas, with limited attention to county-level analyses, particularly regarding the complex interactions between climate, topography, and human activities. This study aims to address this gap by investigating the spatiotemporal evolution and multidimensional driving factors of EEQ in 107 counties of Shaanxi Province, China. Using the Google Earth Engine (GEE) platform and MODIS imagery, along with methods such as the Remote Sensing Ecological Index (RSEI), Hurst exponent, and GeoDetector, this study analyzed the evolutionary characteristics and driving mechanisms of county-level EEQ, and explored improvement and management strategies for different types of county EEQ within the framework of dual carbon goals. The results indicate that: 1) From 2000 to 2020, the overall EEQ in Shaanxi Province showed a fluctuating upward trend, improving from a moderate level to a good level, although some counties experienced slight degradation from 2010 to 2020. 2) The spatial distribution of county-level EEQ displayed a “low-high-low-high” gradient from north to south, indicating superior ecological conditions in the southern and central-northern counties, while northern regions faced significant ecological challenges. 3) The future trend of EEQ in Shaanxi Province is expected to be one of continuous improvement, although attention must be paid to the ongoing degradation risks in highly urbanized areas. 4) The spatial differentiation of county-level EEQ is primarily driven by climate factors and influenced by the synergistic effects of multiple factors. For counties with varying levels of EEQ, it is essential to comprehensively consider the interactions between climate, topography, and human factors, and to implement tailored carbon sequestration enhancement strategies. The results not only propose targeted approaches to reinforce carbon storage but also offer valuable policy guidance, thereby making a significant contribution to achieving the dual carbon goals at the county level.